2022
DOI: 10.1039/d1qm00678a
|View full text |Cite
|
Sign up to set email alerts
|

Layered tungsten-based composites and their pseudocapacitive and electrocatalytic performance

Abstract: The WS2–g-C3N4 composite was synthesized for pseudocapacitive and hydrogen evolution reaction measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…According to a new study, a method to obtain heterostructured composites including of transition metal dichalcogenide, WS 2 , and g-C 3 N 4 was introduced. [174] A facile solvothermal method followed by sulfidation was used to prepare WS 2 À g-C 3 N 4 composites with surface vacancies. According to obtained results of both experimental and computational studies, WS 2 and g-C 3 N 4 demonstrated the preferential bonding and interfacial interactions, which optimize the electronic structure, ameliorates electrochemical performance and also charge transfer.…”
Section: G-c 3 N 4 Hybrid Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a new study, a method to obtain heterostructured composites including of transition metal dichalcogenide, WS 2 , and g-C 3 N 4 was introduced. [174] A facile solvothermal method followed by sulfidation was used to prepare WS 2 À g-C 3 N 4 composites with surface vacancies. According to obtained results of both experimental and computational studies, WS 2 and g-C 3 N 4 demonstrated the preferential bonding and interfacial interactions, which optimize the electronic structure, ameliorates electrochemical performance and also charge transfer.…”
Section: G-c 3 N 4 Hybrid Electrocatalystsmentioning
confidence: 99%
“…In this line the NiTe-HfTe 2 /g-C 3 N 4 shows the lowest Tafel slope (75 mV dec À 1 ) between other prepared samples and close to the Pt/C as the known a standard electrocatalyst (41 mV dec À 1 ). [174] Copyright (2022), with permission from Royal Society of Chemistry.…”
Section: G-c 3 N 4 Hybrid Electrocatalystsmentioning
confidence: 99%
“…In this regard, considerable research efforts have been made towards designing and synthesizing various high-performance pseudocapacitive anode materials, such as Fe 2 O 3 , 9 Fe 3 O 4 , 10 Co 3 O 4 , 11 V 2 O 5 , 12 MoO 3 , 13 and transition-metal sulfides, 14,15 in recent times. Among them, transition metal sulfides such as WS 2 , 16 FeS 2 , 17 MoS 2 , 18 CuS, 19 CoS, 20 and NiS [21][22][23][24][25][26][27][28][29][30][31] have recently gained more interest and have been widely used as the anode materials for supercapacitors due to their low electronegativity, excellent electrical conductivity, high specific capacitance, and rich electrochemical redox sites in comparison with their oxide counterparts. Hou et al 21 reported the first use of NiS as a supercapacitor electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, breaking through a new synthetic concept is urgently necessary, which is to decrease the size of bulky MOFs into low-dimensional materials, especially ultrathin 2D MOFs, also called metalorganic layers (MOLs), which are gaining increasing attraction. 40 On the one hand, decreasing the size leads to the minimization of the photocarrier transport distance in MOLs, then promoting photogenetic charge transfer rapidly, [41][42][43][44][45][46][47][48][49] while on the other, the structure of MOLs not only increases the specific surface area of the catalyst but also exposes more coordinatively unsaturated metal sites on the surfaces. Both are beneficial to HER catalytic kinetics.…”
Section: Introductionmentioning
confidence: 99%